Pengaruh Penggunaan Surat Naskah Dinas Elektronik terhadap Kinerja Karyawan di KPP Pratama Kendari - Muchlis, Wildy De Partie; Emilda, Emilda (Jurnal Nasional Manajemen Pemasaran dan SDM, 2023)
The purpose of this study was to determine the effect of using electronic official document letters on the performance of employees at the Primary Kendari Tax Service Office (KPP). The Nadine application was adopted to support efficiency and effectiveness in official document administration. The data collection technique is through a questionnaire given to employees at KPP Pratama Kendari who have used the Nadine application. The results of this study indicate that the implementation of the Nadine application has a positive impact on improving staff performance at KPP Pratama Kendari. Nadine's application has an impact on improving performance including increasing official document production, decreasing response time to incoming letters, reducing error rates in writing and filing official scripts, improving the quality of public services, using electronic signatures, increasing data and information security, and ease of access. It is hoped that this research can be used as input for KPP Pratama Kendari to continue to increase the use of electronic official document letters as an effort to improve employee performance in the office environment.